Avaliação de um programa de intervenção de habilidades sociais educativas parentais: um estudo-piloto - Bolsoni-Silva, Alessandra Turini [UNESP]; Salina-Brandão, Alessandra; Versuti-Stoque, Fabiana Maris [UNESP]; Rosin-Pinola, Andréa Regina (Conselho Federal de Psicologia, 2008)
Estudos têm apontado relações entre déficits de habilidades sociais educativas de pais e problemas de comportamento de seus filhos. Nesse sentido, esta pesquisa visa a descrever os efeitos de um procedimento de intervenção com pais, o qual pretendeu promover suas habilidades sociais educativas. Participaram dois pais e sete mães, que elegeram o filho com o qual descreveram ter maiores dificuldades de relacionamento. Para a avaliação: 1) das dificuldades dos pais, foi utilizada uma entrevista estruturada, e 2) dos procedimentos de intervenção, foram utilizados: a) questionário de habilidades sociais educativas parentais (QHSE-P) e b) inventário de habilidades sociais (IHS-Del Prette). Os resultados das comparações pré e pós-intervenção do IHS-Del Prette mostraram aumento no escore dos grupos; as comparações do QHSE-P apontaram aquisições de diversas habilidades sociais educativas: expressar sentimentos positivos, agradecer elogios, dizer não e negociar limites. Discute-se a necessidade de procedimentos de promoção de habilidades sociais educativas para ampliar o repertório social parental.

Studies have pointed the relations between the deficit of social education skills of the parents and the behavior problem of their children. In relation to this subject, this research has the objective of describing the effects of the intervention process in parents aiming to promote their social educative skills. Two fathers and seven mothers contributed with this research choosing among their children the one with whom they have more relationship difficulties. For the evaluation: 1) for the parents difficulties, a structured interview was used and 2) for the intervention procedures, it was used a) a parental social educative skills questionnaire and b) a list of social skills. The results of the comparisons made before and after the intervention of the IHS-Del Prette show a rising on the score of the groups; in the comparisons of the QHSE-P it was verified the acquisitions of educative social skills: to express positive feelings, to thank praises, to deny and negotiate limits. It is discussed the need of procedures that may lead to the promotion of educative social skills as a way to increase the social knowledge of the parents.
Evaluation of an intervention of parental educative social skills program: a pilot study
Keywords: Treinamento de habilidades sociais; Habilidades sociais educativas; Intervenção com pais; Interação pais-filhos; Training of social abilities; Educative social skills; Intervention with parents; Interaction parents-children